Effectiveness and cost-effectiveness of a virtual community of practice to improve the empowerment of patients with ischaemic heart disease: study protocol of a randomised controlled trial. Issue 10 (12th October 2020) - González-González, Ana Isabel; Perestelo-Pérez, Lilisbeth; Koatz, Débora; Ballester, Marta; Pacheco-Huergo, Valeria; Ramos-García, Vanesa; Torres-Castaño, Alezandra; Rivero-Santana, Amado; Toledo-Chávarri, Ana; Valcárcel-Nazco, Cristina; Mateos-Rodilla, Juana; Obaya-Rebollar, Juan Carlos; et al.
Abstract : Introduction: Virtual Communities of Practice (VCoP) or knowledge-sharing virtual communities offer ubiquitous access to information and exchange possibilities for people in similar situations, which might be especially valuable for the self-management of patients with chronic diseases. In view of the scarce evidence on the clinical and economic impact of these interventions on chronic conditions, we aim to evaluate the effectiveness and cost-effectiveness of a VCoP in the improvement of the activation and other patient empowerment measures in patients with ischaemic heart disease (IHD). Methods and analysis: A pragmatic randomised controlled trial will be performed in Catalonia, Madrid and Canary Islands, Spain. Two hundred and fifty patients with a recent diagnosis of IHD attending the participating centres will be selected and randomised to the intervention or control group. The intervention group will be offered participation for 12 months in a VCoP based on a gamified web 2.0 platform where there is interaction with other patients and a multidisciplinary professional team. Intervention and control groups will receive usual care. The primary outcome will be measured with the Patient Activation Measure questionnaire at baseline, 6, 12 and 18 months. Secondary outcomes will include: clinical variables; knowledge (Questionnaire of Cardiovascular Risk Factors), attitudes (Self-efficacy Managing Chronic Disease Scale), adherence to the Mediterranean diet (Mediterranean Diet Questionnaire), level of physical activity (International Physical Activity Questionnaire), depression (Patient Health Questionnaire), anxiety (Hospital Anxiety Scale-A), medication adherence (Adherence to Refill Medication Scale), quality of life (EQ-5D-5L) and health resources use. Data will be collected from self-reported questionnaires and electronic medical records. Ethics and dissemination: The trial was approved by Clinical Research Ethics Committee of Gregorio Marañón University Hospital in Madrid, Nuestra Señora de Candelaria University Hospital in Santa Cruz de Tenerife and IDIAP Jordi Gol in Barcelona. The results will be disseminated through workshops, policy briefs, peer-reviewed publications, local/international conferences. Trial registration number: ClinicalTrials.gov Registry (NCT03959631 ). Pre-results.